A comprehensive assessment of environmental pollution by means of heavy metal analysis for oysters' reefs at Hab River Delta, Balochistan, Pakistan. (April 2020) - Aslam, Sadar; Chan, Malik Wajid Hussain; Siddiqui, Ghazala; Boczkaj, Grzegorz; Kazmi, Syed Jamil Hasan; Kazmi, Mohib Reza
Abstract: The heavy metal pollution status of oyster reefs has been assessed with respect to ten metals pollutants in seawater, sediments, and tissues of above two oysters (soft tissues and shells) for assessing the pollution status in a short food chain in Hab River Delta. The results showed that heavy metals accumulated in M . bilineata were higher than those in M . cuttackensis . Simultaneously, the population of M . bilineata species has been ironically decreasing as a results of high pollution. The determined concentrations revealed a significant differences in their profiles among sediments, seawater and bioaccumulation in tissues and shells of two native oysters. The present study also compared these metal concentrations with national and international database by applying different pollution indices. Heavy metals in all samples were above the national environmental quality standards (NEQS-Pakistan). High level of pollution with an alarming condition of Hab River Delta need more attention for coastal management. Highlights: The first report of concentrations of heavy metals in two native oysters The pollution status has been monitored with ten kind of metals pollutants. Concentrations were showed significant differences among all samples. More heavy metals were accumulated in tissues of M . bilineata than M . gryphoides . Heavy metals in all samples were above the local environmental quality standards.